2014
DOI: 10.1242/dev.113415
|View full text |Cite
|
Sign up to set email alerts
|

Programmed cell cycle arrest is required for infection of corn plants by the fungus Ustilago maydis

Abstract: Ustilago maydis is a plant pathogen that requires a specific structure called infective filament to penetrate the plant tissue. Although able to grow, this filament is cell cycle arrested on the plant surface. This cell cycle arrest is released once the filament penetrates the plant tissue. The reasons and mechanisms for this cell cycle arrest are unknown. Here, we have tried to address these questions. We reached three conclusions from our studies. First, the observed cell cycle arrest is the result of the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 48 publications
1
28
1
Order By: Relevance
“…In M. oryzae, S phase is necessary to initiate appressorium differentiation, while M phase and autophagy in conidia are essential for the development of functional appressoria that form the penetration peg (Veneault-Fourrey et al, 2006;Saunders et al, 2010a). By contrast, in U. maydis, cell cycle arrest in G2 phase is required for the induction of appressorium formation, and the arrest is held until the infective dikaryotic hyphae penetrate host plants (Castanheira et al, 2014). Thus, M. oryzae and U. maydis have distinctive mechanisms of appressorium development that are coordinated with proper cell cycle progression.…”
Section: A Role For Bub2/bfa1 In Infection-related Morphogenesis and mentioning
confidence: 99%
“…In M. oryzae, S phase is necessary to initiate appressorium differentiation, while M phase and autophagy in conidia are essential for the development of functional appressoria that form the penetration peg (Veneault-Fourrey et al, 2006;Saunders et al, 2010a). By contrast, in U. maydis, cell cycle arrest in G2 phase is required for the induction of appressorium formation, and the arrest is held until the infective dikaryotic hyphae penetrate host plants (Castanheira et al, 2014). Thus, M. oryzae and U. maydis have distinctive mechanisms of appressorium development that are coordinated with proper cell cycle progression.…”
Section: A Role For Bub2/bfa1 In Infection-related Morphogenesis and mentioning
confidence: 99%
“…The dikaryon is cell cycle arrested (Castanheira et al, 2014) and is able to invade the plant via a specialized infection structure, the appressorium. Appressoria allow direct invasion of epidermal plant cells in a process which is likely aided by plant cell wall degrading enzymes and plant cell wall loosening.…”
Section: Introductionmentioning
confidence: 99%
“…Mitotic entry is considered to be sufficient to initiate appressorium maturation but exit from mitosis is required only for plant infection (Saunders et al 2010). In U. maydis, cell cycle regulation has been shown to be tightly regulated during plant infection (Castanheira et al 2014). Recently, we found that the wheat scab fungus F. graminearum has two CDC2 kinase genes.…”
Section: Discussionmentioning
confidence: 99%